Coupling effects of water and nitrogen on photosynthetic characteristics, nitrogen uptake, and yield of sunflower under drip irrigation in an oasis - Wang, Tianyu; Wang, Zhenhua; Wu, Qiang; Zhang, Jinzhu; Quan, Lishuang; Fan, Bihang; Guo, Li (International Journal of Agricultural and Biological Engineering, 2021)
An experiment was conducted in an oasis area in northwest China to assess the coupling effects of water and nitrogen supply through drip irrigation on photosynthetic characteristics, nitrogen uptake, and yield of sunflower (Helianthus annuus L.), as well as the nitrate distribution in the root-zone soil. The experiment included three irrigation levels (210 [W1], 300 [W2], and 390 [W3] mm), three nitrogen levels (162 [N1], 232 [N2], and 302 [N3] kg/hm2), and control treatment (no fertilization during whole growth period and only irrigated at the budding stage). A nitrogen content over-accumulation in the soil was observed under the low irrigation amount with high fertilizer supply, which cannot enhance the sunflowers’ absorption of nitrogen. Excessive irrigation caused leach of the soil nitrogen, reduced nitrogen content in the root-zone soil (0-40 cm) and limited nitrogen uptake by the crop. Although low irrigation amount with high fertilizer supply can increase the nitrogen content in the soil, it cannot enhance the sunflowers’ absorption of nitrogen. At the vegetative stage of sunflower growth, the accumulation of nitrogen in the organs was mainly concentrated in the leaves, while it was transferred to the flower disk at the reproductive growth stage. Reasonable coupling of water and nitrogen improved the transport of nitrogen from leaves and stems to the flower disk aromoted the formation of yield components. Six regression equations were established with irrigation and fertilization amount as independent variables, and seed rate, seed weight per flowerdisk, 1000 grain weight, yield, water use efficiency and nitrogen partial factor productivity as dependent variables, respectively. Multiple regression and spatial analysis suggested that the irrigation amount of 241.62- 253.35 mm and the fertilization application of 202.02-209.40 N kg/hm2 was a good irrigation strategy, under which all six factors exceed 75% of their maxima, and the yield of sunflower reached 3 229.3 kg/hm2. Keywords: fertilization, Helianthus annuus L., irrigation management, nitrogen transformation, nutrient uptake, Xinjiang DOI: 10.25165/j.ijabe.20211405.6399 Citation: Wang T Y, Wang Z H, Wu Q, Zhang J Z, Quan L S, Fan B H, et al. Coupling effects of water and nitrogen on photosynthetic characteristics, nitrogen uptake, and yield of sunflower under drip irrigation in an oasis. Int J Agric & Biol Eng, 2021; 14(5): 130–141.